m-Polar Fuzzy Hyperideals in LA-Semihypergroups - Ahmed Elmoasry; Naveed Yaqoob (International Journal of Analysis and Applications, 2019)
In this paper, we initiate a study of m-polar fuzzy sets in hyperstructure theory, particularly in left almost semihypergroups. We define an m-polar fuzzy left (right, two sided) hyperideal in a left almost semihypergroup and provided some results on these m-polar fuzzy left (right, two sided) hyperideals.